Viabilidade e vigor de sementes de soja em função do Tratamento industrial de semente durante o armazenamento Em ambientes distintos - (:unkn) unknown (Universidade Estadual de Goiás, 2018)
Industrial seed treatment (IST) is an economically efficient technique in agricultural production, providing protection against pests and initial pathogens. However, the real effects of pesticides on the quality of soybean seeds are still poorly known, since the adoption of the system is still recent by soybean farmers. Thus, the objective of this work was to evaluate the physiological quality of soybean seeds, treated or not, with mixtures of insecticides / fungicides, and stored for 240 days in different environments. The experimental design was completely randomized, distributed in a factorial scheme 5 x 2 x 6, with four replications. The plots treatments were composed of soybean seeds belonging to cultivar M - 7739 IPRO, treated with six different mixtures of insecticide / fungicide products {(Cruiser® - Tiametoxam – 200 mL + Bio Cromo – 100 mL); (Amulet® - Fipronil - 100 mL + Bio Cromo – 100 mL); (Maxim Advanced® - Metalaxil-M; Tabendazol; Fludioxonil – 100 mL + Bio Cromo – 100 mL ); (Cruiser® - Tiametoxam – 200 mL + Maxim Advanced® - Metalaxil-M; Tiabendazol; Fludioxonil – 100 mL + Bio Cromo – 100mL ); (Maxim Advanced® - Metalaxil-M; Tabendazol; Fludioxonil – 100 mL + Amulet® - Fipronil - 100 mL + Bio Cromo – 100mL); (untreated control)} stored in two environments {(laboratory - uncontrolled and cold chamber - with control (10 ± 2 ° C, 45 ± 2% RH)} during eight months of storage, with five evaluation times (0, 2, 4, 6 and 8 months). The following tests were performed: water content, germination, first count, seedling length, dry seedlings mass and emergency speed index. The cold storage chamber generally been capable of maintaining the viability of soybean seeds treated with insecticide/fungicide Tiametoxam, Fipronil, Metalaxil-M; Tiabendazol; Fludioxonil, mixed or not, within the marketing standard for up to 60 days. Chemical treatments negatively affect the germination potential of soybeans throughout storage, regardless of the environment.
Keywords: Glycine max L.; Merrill; Qualidade de semente; Sanidade; TIS; Glycine max L.; Quality of seed; Sanity; TIS; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA